AB0562 CARDIOVASCULAR RISK FACTORS AND FRAMINGHAM RISK SCORE IN PRIMARY SJÖGREN SYNDROME PATIENTS: A COMPARATIVE STUDY WITH MATCHED CONTROLS. (June 2019) - Silva, Joana; Faria, Daniela; Neves, Joana; Cerqueira, Marcos; Rodrigues, Joana; Azevedo, Soraia; Tavares-Costa, José; Teixeira, Filipa; Afonso, Carmo; Peixoto, Daniela
Abstract : Background: The association between cardiovascular (CV) risk and chronic systemic inflammatory diseases has been an issue of debate. There is compelling evidence of increased CV morbidity in conditions such rheumatoid arthritis (RA) and systemic lupus erythematous (SLE) (1). Primary Sjögren's syndrome (pSS) is a chronic immune-mediated disease characterized by glandular and systemic manifestations, sharing clinical and immunological similarities with RA and SLE. However, in pSS patients the weight of cardiovascular disease attributed to traditional CV risk factors remains unclear. Objectives: To determine the prevalence of traditional CV risk factors and long-term CV events based on the risk prediction tool of the Framingham risk score (FRS) in pSS patients. Methods: The study included patients diagnosed with pSS, fulfilling both the 2016 ACR/EULAR and 2002 AECG criteria for the disease, followed-up at our Rheumatology department and 49 age and sex-matched controls. Inclusion criteria were age 30 to 74 and no history of CV events in order to calculate the FRS. In total, 46 out of 54 patients were eligible for the study. Data on the prevalence of traditional CV risk factors (diabetes, arterial hypertension and smoking), systolic blood pressure (SBP) values, total and high-density lipoprotein (HDL) cholesterol levels were collected and compared between groups. The 10-year risk for CV events according to FRS was calculated and means of patients and controls were compared. Parametric and nonparametric tests were used and the level of significance was defined as p<0.05. Results: The mean age of pSS patients and healthy individuals was 58.0±11.6 and 54.1±13.6 years, respectively. The prevalence of arterial hypertension was higher in pSS patients than controls (52.2% versus 24.5%, p=0.005). The prevalence of diabetes and smoking did not differ significantly between the two groups (p=0.674 and p=0.949, respectively). The SBP values, total and HDL cholesterol levels were also similar between pSS patients and healthy subjects (p=0.063, p=0.413 and p=0.217, respectively). Mean 10-years risk for CV events assessed by FRS was 11.8±8.3 for pSS patients and 7.8±8.4 for matched controls, with statistically significant difference (p=0.013). Conclusion: In our study, pSS patients had a higher prevalence of arterial hypertension, which is in agreement with the M. Juarez et al (1) study. Although there were no significant differences in the other traditional CV risk factors, the results showed an increased 10-year risk for major CV events based on FRS assessment in pSS patients in comparison to age and sex-matched controls. References: [1] M. Juarez, et al. Cardiovascular Risk Factors in Women With Primary Sjogren's Syndrome: United Kingdom Primary Sjogren's Syndrome Registry Results. Arthritis Care & Research. Vol. 66, No. 5, May 2014, pp 757-764. Disclosure of Interests: None declared